К вопросу подобия технологических процессов производственно-технических систем - Азаренков, Н.А.; Пигнастый, О.М.; Ходусов, В.Д. (Доповіді НАН України, 2011)
З використанням статистичного підходу в моделюванні технологічних процесів виробничо-технічних систем отримані характерні числа для опису технологічних процесів. Визначені критерії подібності технологічних процесів. With the use of the statistical approach in the design of technological processes of the industrial technical systems, the characteristical numbers are obtained for the description of technological processes. The similarity criteria of technological processes are defined.